(untitled) (Global Journal of Science Frontier Research, 2024)
Environmental management is the management of activities that may have an impact on the environment 1 It aims to limit polluting emissions and risks to the environment and to save natural resources 2 Often unsuspected and therefore without us always realizing it all economic activities can have a considerable impact on the environment 3 Indeed the manufacture of products requires the extraction of raw materials and the use of water and energy 4 Similarly activities associated with the manufacturing process such as maintenance transportation all have environmental impacts 5 The environmental management system is a progress tool that integrates the environmental dimension into an organization s strategy leading it to set objectives achieve and maintain performance through effective management and promotes anticipation the forecast There is a multitude of guides allowing self-diagnosis by the organization and which make it possible to make an environmental assessment ISO 14001 is the environmental management standard created by the international organization for standardization 6 It defines the requirements of a global environmental management system for self-reporting or certification purposes 7 It is organized in 17 points modeled on quality management well known for 34 years in the industry The standard does not establish any absolute requirement for environmental performance other than a commitment to environmental policy to comply with legislation and the principle of continuous improvement 8